Stop-Frame Filming and Discovery of Reactions at the Single-Molecule Level by Transmission Electron Microscopy - Chamberlain, Thomas W; Biskupek, Johannes; Skowron, Stephen T; Markevich, Alexander V; Kurasch, Simon; Reimer, Oliver; Walker, Kate E; Rance, Graham A; Feng, Xinliang; Müllen, Klaus; Turchanin, Andrey; Lebedeva, Maria A; et al. (ACS nano, 2017)
We report an approach, named chemTEM, to follow chemical transformations at the single-molecule level with the electron beam of a transmission electron microscope (TEM) applied as both a tunable source of energy and a sub-angstrom imaging probe. Deposited on graphene, disk-shaped perchlorocoronene molecules are precluded from intermolecular interactions. This allows monomolecular transformations to be studied at the single-molecule level in real time and reveals chlorine elimination and reactive aryne formation as a key initial stage of multistep reactions initiated by the 80 keV e-beam. Under the same conditions, perchlorocoronene confined within a nanotube cavity, where the molecules are situated in very close proximity to each other, enables imaging of intermolecular reactions, starting with the Diels–Alder cycloaddition of a generated aryne, followed by rearrangement of the angular adduct to a planar polyaromatic structure and the formation of a perchlorinated zigzag nanoribbon of graphene as the final product. ChemTEM enables the entire process of polycondensation, including the formation of metastable intermediates, to be captured in a one-shot “movie”. A molecule with a similar size and shape but with a different chemical composition, octathio[8]circulene, under the same conditions undergoes another type of polycondensation via thiyl biradical generation and subsequent reaction leading to polythiophene nanoribbons with irregular edges incorporating bridging sulfur atoms. Graphene or carbon nanotubes supporting the individual molecules during chemTEM studies ensure that the elastic interactions of the molecules with the e-beam are the dominant forces that initiate and drive the reactions we image. Our ab initio DFT calculations explicitly incorporating the e-beam in the theoretical model correlate with the chemTEM observations and give a mechanism for direct control not only of the type of the reaction but also of the reaction rate. Selection of the appropriate e-beam energy and control of the dose rate in chemTEM enabled imaging of reactions on a time frame commensurate with TEM image capture rates, revealing atomistic mechanisms of previously unknown processes.